Studies towards a stereocontrolled synthesis of the tricarboxylate core of the zaragozic acids-squalestatins by a cycloaddition-rearrangement strategy - Hodgson, D; Villalonga-Barber, C (2000)
Reaction of diazoketodiester 11 with methyl glyoxylate in toluene in the presence of catalytic rhodium(II) acetate gives predominantly the 6,8- dioxabicyclo[3.2.1]octane 13. Acid-catalysed rearrangement of the corresponding alcohol 14 favours at equilibrium the 2,8- dioxabicyclo[3.2.1]octane skeleton 15 of the zaragozic acids-squalestatins. (C) 2000 Elsevier Science Ltd.